Gestión administrativa del talento humano para la innovación sostenible en pymes constructoras colombianas. (2022)
Within the tasks of the administration in the construction companies is that of establishing objectives and policies by means of which the purpose is achieved through the best possible procedures, for which its management must be directed to the greatest concern and need for citizenship and the planet in the present times, due to the great contamination that is caused both to the environment that surrounds us, and to the health of the people themselves. Therefore, it is important to innovate in a sustainable way in our territory, caring for the environment, conserving resources, and protecting the fauna and flora. Due to all this current problem, it is essential and necessary to carry out constructions that have the objective of integrating environmental and social criteria within the thousands of projects that positively impact the inhabitants, societies and areas, which are essential for the benefit of the environment.